Association of Bleeding Severity With Mortality in Extended Thromboprophylaxis of Medically Ill Patients in the MAGELLAN and MARINER Trials. Issue 19 (7th April 2022) - Spyropoulos, Alex C.; Raskob, Gary E.; Cohen, Alexander T.; Ageno, Walter; Weitz, Jeffrey I.; Spiro, Theodore E.; Lu, Wentao; Lipardi, Concetta; Albers, Gregory W.; Elliott, C. Gregory; Halperin, Jonathan L.; Hiatt, William R.; et al.
Abstract : Background: Extended thromboprophylaxis has not been widely implemented in acutely ill medical patients because of bleeding concerns. The MAGELLAN (Multicenter, Randomized, Parallel Group Efficacy and Safety Study for the Prevention of Venous Thromboembolism in Hospitalized Medically Ill Patients Comparing Rivaroxaban With Enoxaparin) and MARINER (Medically Ill Patient Assessment of Rivaroxaban Versus Placebo in Reducing Post-Discharge Venous Thrombo-Embolism Risk) trials evaluated whether rivaroxaban compared with enoxaparin or placebo could prevent venous thromboembolism without increased bleeding. We hypothesized that patients with major bleeding but not those with nonmajor clinically relevant bleeding would be at an increased risk of all-cause mortality (ACM). Methods: We evaluated all bleeding events in patients taking at least 1 dose of study drug and their association with ACM in 4 mutually exclusive groups: (1) no bleeding, or first event was (2) nonmajor clinically relevant bleeding, (3) major bleeding, or (4) trivial bleeding. Using a Cox proportional hazards model adjusted for differences in baseline characteristics associated with ACM, we assessed the risk of ACM after such events. Results: Compared with patients with no bleeding, the risk of ACM for patients with nonmajor clinically relevant bleeding was not increased in MARINER (hazard ratio, 0.43; P =0.235) but was increased in MAGELLAN (hazard ratio, 1.74; P =0.021). Major bleeding was associated with a higher incidence of ACM in both studies, whereas trivial bleeding was not associated with ACM in either study. Conclusions: Patients with major bleeding had an increased risk of ACM, whereas nonmajor clinically relevant bleeding was not consistently associated with an increased risk of death. These results inform the risk-benefit calculus of extended thromboprophylaxis in medically ill patients. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: MAGELLAN, NCT00571649. URL: https://www.clinicaltrials.gov ; Unique identifier: MARINER, NCT02111564.